STUDY ON CRACK PROPAGATION MECHANISM OF TUNGSTEN UNDER UNIAXIAL LOADING - MA Lei; HUANG JunYuan (Jixie qiangdu, 2020)
The microscopic mechanism of crack propagation behavior of single crystal tungsten under uniaxial loading was investigated by means of molecular dynamics. The effects of temperature and crystal orientation on crack propagation were analyzed. The results show that at different temperatures,the main deformation mechanism of the crack in the [001] direction were slip band,dislocation and blunting. As the temperature increases,the yield strength decreased as the crack propagation. At300 K and 500 K,the crack showed a rapid expansion after yield deformation,while at 700 K and 900 K,the crack showed a secondary yielding phenomenon. Besides,crack models of different crystal orientation were established. The results showed that the yield strength of the crack was the largest when stretching in the [111] direction,[110] is the second,[001] is the smallest,and the yielding platform appeared in the stress-strain curve of the [110]crystal orientation,indicating better plasticity and tensile properties,the main deformation mechanism were slip bands when the crack propagates germination. The crack in[111]orientation formed dislocations during the expansion process,and the crack expanded in the form of blunting and voids.The above showed that the crack in different crystal orientation had different microstruction evolution at crack tip.